The thermal establishments at Lambése city (Tazoult) The Romane Camp Baths as a Model - Hussein, Mohammed Al-Sharif (The Algerian Historical Journal, 2026)
The city of Lambése (Tazoult), is one of the most important ancient cities in eastern Algeria, which witnessed a remarkable development in its architecture during the ancient period, due to its important strategic location, especially during the Severian periode, where it was the military capital of Numidia. This is clearly evidenced by the physical evidence of the ancient city's architecture revealed by archaeological research and excavations. In particular, the baths of the Roman camp, which is considered an important landmark within the urban fabric of this city. Therefore, we shed light on a relevant elements, including the, architecture of the camp's baths in terms of modelling and dating, based on archaeological and historical data.